Assessment of “Musa spp” Fibre Inclusion on the Strength and Sorption Properties of Cement Bonded Particle Board - Jacob Mayowa Owoyemi; Hazzan Adigun (CV. Literasi Indonesia, 2021)
The increase in demand for wood for various purposes has put serious pressure on Nigeria’s forest with its attendant fall in the supply of solid wood for construction purposes. As an alternative, non-woody material like banana stem fibre is being investigated for the production of Cement Bonded Particle Board (CBPB). The sorption and strength properties of CBPB from Musa spp fibre were assessed. The board samples were formed using cement to materials mixing ration of 2:1 and 3:1 and blending proportions of sawdust and banana fibre using ordinary Portland cement as a binder. Physical and Mechanical properties of boards produced from stem using were investigated. The influence of blending proportion (B.P) and mixing ratio (MR) on Density, Water Absorption (WA), Thickness Swelling (TS), Linear Expansion, Modulus of Rupture (MOR), and Modulus of Elasticity (MOE) were determined. The results of sorption properties showed that for immersion at 24, 48, and 72 hours, WA, TS, and LE decreased with an increase in mixing ratio. MOE mean values ranged between 293.65 and 2367.01 N/mm2 for 2:1 and 250.99 and 2009.28 N/mm2 for 3:1 while MOR values ranged between 2.55 and 7.592 N/mm2 for 2:1 and ranged from 0.55 to 1.40 N/mm2 for 3:1 respectively. The result proved that banana fibre is suitable for the production of panel products with enhanced strength properties.